Molecular Detection Of Mycoplasma Spp. Associated With The Female Reproductive Tract Of Cattle And Buffaloes (Applied Biological Research, 2015)
The present study was aimed to detect Mycoplasma spp. associated with  the female reproductive tract of cattle and buffaloes in Punjab (India).  Out of 65 samples comprising of uterine discharges, vaginal mucus and  foetal stomach contents, 21 were positive for Mycoplasma spp. by genus  specific PCR using primers based on 16S rDNA of Mycoplasma spp. An  amplification band of 270-bp was obtained in all the positive samples.  The overall prevalence of Mycoplasma spp. in cattle and buffaloes was  32.3% whereas the prevalence was 24.61 and 7.69% in cattle and  buffaloes, respectively. Maximum prevalence of 21.7% was seen in HF  breed of cattle and 15.78% in Murrah breed of buffaloes. Cattle and  buffaloes in age group 4-6 years and 6-8 years were found more positive for Mycoplasma spp.
Keywords: Buffaloes; cattle; Mycoplasma; PCR; uterine discharges; vaginal mucus